Integrating applied parasitological and molecular epidemiological methodologies to investigate the capacity of Haemonchus contortus to over‐winter on pasture in Scotland. (19th February 2021) - Bartley, David J.; Andrews, Leigh; Melville, Lynsey A.; McBean, David; Skuce, Philip; Morrison, Alison A.
Abstract: Background : The Barber's Pole worm, Haemonchus contortus is of major concern to sheep producers, particularly in the southern hemisphere. This nematode is also commonly found in many sheep flocks in Northern hemisphere countries but is generally not associated with acute clinical pathology. As with other nematode species, the pattern of disease is changing in the United Kingdom. Changes in management practices, climate, anthelmintic resistance prevalence and parasite adaptation are possible factors thought to be responsible for this. Methods : In the present study, a combination of traditional applied parasitological and molecular species identification techniques were used to assess the capability of H. contortus infective larvae to over‐winter on pasture and infect lambs in early spring. Results : Adult and inhibited H. contortus worms were identified in previously worm‐free tracer lambs that had grazed contaminated pasture in late winter/early spring (February/March). Conclusion : The study illustrated the benefit of using classical applied parasitology techniques in conjunction with molecular species identification methods to explore the epidemiology of gastro‐intestinal nematodes of livestock. This study also demonstrated that larvae were able to survive over‐winter, albeit in small numbers, and potentially contaminate pastures earlier than previously considered in northern regions of the UK.